Factor analysis on the agricultural technology adoption and arabica coffee productivity in Kintamani District, Bangli Regency - Sasrawan, I Putu Hedi; Yuliarmi, Ni Nyoman (International research journal of management, IT and social sciences, 2021)
The economy of Bali requires diversification through optimization of the agricultural sector. Arabica coffee is a potential commodity to diversify the agricultural sector and maximizing the potential of the highland at Kintamani District, Bangli Regency. Productivity must be improved considering that agricultural land in Bali is limited and many have been converted to residential or commercial use. According to evolutionary theory, agricultural productivity can be increased by technology. However, the technology application needs to be supported by adequate human resources and factors of production. The purpose of this study was to analyze the effect of farmer characteristics, production factors, and agricultural technology adoption on productivity, as well as to analyze the indirect effect of farmer characteristics and production factors on productivity through agricultural technology adoption. The area sampling method obtained a total sample of 98 farmers in 10 villages in the Kintamani District, Bangli Regency. Area sampling is carried out in two stages, first is determining regional samples and determining the respondents in each area by accident. The data collection methods are observation, structured interviews using questionnaires, and in-depth interviews. The data analysis technique used partial least square.